2017
DOI: 10.1063/1.4984772
|View full text |Cite
|
Sign up to set email alerts
|

A model of energetic ion effects on pressure driven tearing modes in tokamaks

Abstract: The effects that energetic trapped ions have on linear resistive magnetohydrodynamic (MHD) instabilities are studied in a reduced model that captures the essential physics driving or damping the modes through variations in the magnetic shear. The drift-kinetic orbital interaction of a slowing down distribution of trapped energetic ions with a resistive MHD instability is integrated to a scalar contribution to the perturbed pressure, and entered into an asymptotic matching formalism for the resistive MHD disp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 29 publications
(71 reference statements)
0
14
0
Order By: Relevance
“…A trans ition between the double tearing mode and fishbonelike mode can be triggered, depending on energeticion drive [20]. NIMROD code simulation results suggest the m/n = 2/1 low frequency mode can be driven by energeticions with weak shear in the core and high q min > 1.3 [21], and, subsequently this result is explained by a theoretical model, namely the TM is excited by trapped energeticions via precession resonance [22]. On devices, such as TFTR, neoclassical tearing modes (NTMs) have a chirping character, implying strong interaction with energeticions [23].…”
Section: Introductionmentioning
confidence: 90%
“…A trans ition between the double tearing mode and fishbonelike mode can be triggered, depending on energeticion drive [20]. NIMROD code simulation results suggest the m/n = 2/1 low frequency mode can be driven by energeticions with weak shear in the core and high q min > 1.3 [21], and, subsequently this result is explained by a theoretical model, namely the TM is excited by trapped energeticions via precession resonance [22]. On devices, such as TFTR, neoclassical tearing modes (NTMs) have a chirping character, implying strong interaction with energeticions [23].…”
Section: Introductionmentioning
confidence: 90%
“…Experimentally, the observations on DIII-D reported by Heidbrink et al [22] indicate that some energetic-ion orbits resonate with TMs but that the density of resonances in the phase-space is sparse. Based on a DIII-D hybrid discharge with the weak shear in the core, a theory model proposed by Brennan shows that the resistive m/n = 2/1 mode is driven to be unstable by trapped EPs via precession resonance [23,24]. Despite all this, the study of resonant interaction between EPs and m > 1 resistive instabilities is still quite limited.…”
Section: Hybrid-kinetic Simulation Of Resonant Interaction Between En...mentioning
confidence: 99%
“…and are hence important for achieving advanced operation scenarios with high plasma pressure; on the other hand, they can significantly modify magnetohydrodynamic (MHD) stabilities via the wave-particle interactions. The roles played by EPs in various macroscopic MHD instabilities have been extensively investigated for decades [2][3][4][5][6][7][8][9][10][11][12]. For instance, EPs have been found to stabilize the ballooning mode [2] and the internal kink instability [3].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, EPs do affect the TM by modifying the perturbed parallel current via interaction with either the inner resistive layer, which is generally a non-linear effect [7], or the outer ideal region for linear TMs [8,9]. Interestingly, it has also been reported that the effects of EPs on the TM depend on the magnetic shear [10], i.e. being stabilizing for equilibria with monotonic safety factor profiles (and hence positive shear) [8] while destabilizing for equilibria with slightly reversed magnetic shear in the plasma core [11].…”
Section: Introductionmentioning
confidence: 99%